The level of phonemic hearing in five-year-olds − A study among children from kindergartens in Olsztyn - Osowicka-Kondratowicz, Magdalena (Papers in Linguistics, 2024)
The article is a research report on the level of phonemic hearing development in Olsztyn preschool children as compared to the average results of the reference group (the norm). 144 five-year-old children were assessed in the study. The level of development of phonemic hearing was determined with “The Phonemic Hearing Evaluation Sheet” (Pl. “Karta Oceny Słuchu Fonemowego” (KOSF), Gruba 2016). The level of the analysed phonological function was measured taking into account articulation (measured with “100-word Articulation Test,” Pl. “100 wyrazowy Test Artykulacyjny,” Krajna 2008) as well as lexis and grammar (assessed using “The Language Development Test,” Pl. “Test Rozwoju Językowego (TRJ),” Smoczyńska et al. 2015). Among the examined subsystems, the worst results were obtained as regards phonemic hearing. There were not only more children whose level of phonemic hearing proficiency was assessed as below the typical result for their age, but also there were the fewest children who were above the average as regards this function. The order of the best vs. the worst differentiated phonological oppositions provided by the analysed children was different compared to the previously conducted research by Gruba (2012a: 81–85; 2016). Children from Olsztyn coped the worst with the opposition between oral and nasal vowels (proszki vs. prążki), one of the easiest in Gruba’s (2012a) research. Apart from that, a low level of phonemic hearing did not always correspond to a low level of articulation development.